Analysis of the impact on ACP countries of opening up the EU import market for canned tuna: executive summary - IDDRA (Technical Centre for Agricultural and Rural Cooperation, 2004)
ACP canned tuna producers lost a degree of their comparative advantage over the larger Asian producers when the EU, abiding by a WTO ruling, assigned Thailand, the Philippines and Indonesia a 25,000 tonnes import quota of reduced tariff cannned tuna.